Implementation of Restorative Justice in the Indonesian Criminal Law System - Wala, Gevan Naufal (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Restorative justice is an alternative approach in the criminal law system that is oriented towards restoring social relations between perpetrators, victims, and the community. In Indonesia, the application of this concept has begun to be adopted in various regulations, such as Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, Regulation of the Chief of Police No. 8 of 2021, and Circular of the Attorney General No. 15 of 2020. This article uses a normative legal research method with a descriptive-analytical approach to examine the basic concept of restorative justice, implementation in the field, challenges faced, and solutions to strengthen its application in Indonesia. The results of the discussion show that although the application of restorative justice has shown positive developments in resolving minor criminal cases, challenges such as the retributive paradigm, limited regulations, and lack of understanding of the authorities are still obstacles. Therefore, strengthening national regulations, legal education, and increasing the role of the community are important steps in expanding the application of restorative justice effectively and fairly in Indonesia.